Candida species causing vulvovaginitis among patients in Babcock University Teaching Hospital, Ilishan-Remo, Ogun State: A retrospective cross-sectional study. (2024)
Background: Vulvovaginal candidiasis (VVC) is one of the most common infections in females. In recent decades, reports of incidence of non-albicans candida species causing VVC is increasing and this has led to a lot of therapeutic failures. Thus, this study aimed to detect Candida species among women who presented with VVC in Babcock University Teaching Hospital (BUTH), Ogun State. Methods: This was a cross-sectional retrospective hospital-based study carried out in BUTH. Candida isolates from high vaginal swab of 82 women who presented with VVC at the gynecology and family medicine clinics of the hospital were retrieved for a period of 2 years, January 2019 till December 2020. The isolates were analyzed by standard medical microbiology technique. Information on sociodemographic and behavioral factors were retrieved from clinical case notes. The data were analyzed by IBM SPSS Statistics version 26. Results: The 82 isolates analyzed yielded 87 species of Candida. Out of the 87 isolates of Candida, the albicans species were 50 (57.5%) while the non-albicans were 37 (42.5%). Among the non-albicans species, 16 (43.2%) Candida krusei had the highest frequency while 7 (19.0%) Candida tropicalis had the least and the other isolates that are unidentified by CHROMagaar accounted for 14 (37.8%). Candida albicans was predominant among 12/18 (66.7%) participants with present multiple sex partners. C. albicans was significantly associated with hormonal contraceptives and C. krusei with wearing of tight and nylon underwear, respectively, on bivariate analysis (P < 0.05) Conclusion: C. albicans was the predominant identified species from this study; however, the prevalence of the non-albicans candida species was still high